Travelling Wave Solutions for the KdV-Burgers-Kuramoto and Nonlinear Schrödinger Equations Which Describe Pseudospherical Surfaces - S. M. Sayed; O. O. Elhamahmy; G. M. Gharib (Journal of Applied Mathematics)
We use the geometric notion of a differential system describing surfaces of a constant negative curvature and describe a family of pseudospherical surfaces for the KdV-Burgers-Kuramoto and nonlinear Schrödinger equations with constant Gaussian curvature −1. Travelling wave solutions for the above equations are obtained by using a sech-tanh method and Wu's elimination method.